Effect of Sea Sand Addition on Liquid Limit, Plasticity Index, and CBR of Clay Soil - Ndruru, Fajar Kurniawan; Nasution, Ridwan; Lubis, Yusuf Parlagutan (Trigin Publisher, 2025)
Soil is a composition of grains resulting from weathering of massive rock masses, where the size of each grain can be as large as gravel, sand, silt, clay and uncemented intergranular boxes including organic materials. Laboratory testing includes liquid limit tests, plastic limits, and plasticity index, soil specific gravity, compaction and laboratory CBR to determine soil strength. The method used in this study is the Experimental method, which is a method carried out by conducting experimental activities to obtain data. Based on the results of the research test using clay soil and sea sand, the CBR value with 100% clay soil and 0% sea sand was 5.41% with soil classification A-7-6, 85% clay soil and 15% sea sand obtained a CBR value of 8.82% with soil classification A-4 and 70% clay soil with 30% sea sand obtained a value of 10.55% with soil classification A-2-6. The better CBR value and soil classification are in 70% clay soil and 30% sea sand.